The Role Of Self-Compassion In Psychological Conditions: Narrative Literature Review In Indonesian Research Participants - Herliyana Isnaeni (Publikasi Indonesia, 2023)
Self-compassion is a person's way of loving themselves and accepting themselves. Self-compassion is also a concept of kindness to oneself, especially in times of difficulty or failure. This research method uses a qualitative approach, namely a narrative literature review. There are ten references indexed in the Google Scholar database with a publication range from 2018 to 2023. The references used are research using Indonesian participants. The focus of the discussion is related to self-compassion. This research shows that the role of self-compassion in daily life influences many psychological aspects of various individual characteristics. Several variables are often associated with self-compassion, namely depression, loneliness, well-being, stress, social support, and self-regulation. It is hoped that further research can examine more deeply and broadly the role of self-compassion in various individual characteristics.